2021
DOI: 10.1016/j.drugpo.2020.102789
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of cannabis health information labels among people who use cannabis in the U.S. and Canada

Abstract: Background:The emergence of legal cannabis industries poses a new public health challenge.Health information labels are part of the public health strategy for tobacco and alcohol, but there is limited research on cannabis-related messaging. This study explored perceptions of cannabis health information labels among people who used cannabis in the last 12 months residing in the U.S. and Canada. Methods:The Global Drug Survey (GDS) is a large anonymous cross-sectional web-survey. In GDS2019, respondents were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition to providing clear information about dose and serving sizes, labels should convey health messages to inform consumers of the risks associated with cannabis use. Results of focus groups and surveys have been promising in suggesting that current cannabis users react positively towards the inclusion of health labels on cannabis products, and that health labelling may be effective in changing health-related behaviors ( 77 , 79 81 ). For example, data collected as part of a survey of Canadians aged 16 to 30 years found that about 88% of respondents supported having health warnings on cannabis products, and that pictorial health warnings were perceived as more believable and effective than text-based warnings ( 79 ).…”
Section: Approaches To Minimizing Acute Harms: Recommendations For Pumentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing clear information about dose and serving sizes, labels should convey health messages to inform consumers of the risks associated with cannabis use. Results of focus groups and surveys have been promising in suggesting that current cannabis users react positively towards the inclusion of health labels on cannabis products, and that health labelling may be effective in changing health-related behaviors ( 77 , 79 81 ). For example, data collected as part of a survey of Canadians aged 16 to 30 years found that about 88% of respondents supported having health warnings on cannabis products, and that pictorial health warnings were perceived as more believable and effective than text-based warnings ( 79 ).…”
Section: Approaches To Minimizing Acute Harms: Recommendations For Pumentioning
confidence: 99%
“…Another online experimental study of university students in Alberta, Canada found that viewing cannabis packages with health warnings increased health knowledge ( 80 ). An analysis of data from the 2019 Global Drug Survey (a large international cross-sectional web-based survey) found that health labels may have the most impact among less frequent users of cannabis ( 81 ). However, an important caveat is that many consumers may not read product labels if there is too much information, as demonstrated in focus groups in Colorado and Washington ( 77 ), which supports the need for warnings that are either entirely pictorial or at least have minimal text.…”
Section: Approaches To Minimizing Acute Harms: Recommendations For Pumentioning
confidence: 99%
“…[7][8][9] A survey conducted with cannabis consumers in Canada and the US in the year following nonmedical cannabis legalization in Canada showed survey respondents six text-based warnings. 10 One-third of cannabis consumers indicated they would be "happy" to see health warning messages on cannabis products, and each of the warning messages was rated as believable by between half and three-quarters of consumers. Compared to consumers in the US, those in Canada reported higher levels of support and believability, and perceived the health information as less novel.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors, in their analyses, found that in the absence of an image or logo, the product's attractiveness also decreases (Winstock et al, 2021).…”
Section: Cbd Packaging and Brandingmentioning
confidence: 96%
“…Those with a more luxurious layout have higher consumer interest (Leos‐Toro et al., 2020). Other authors, in their analyses, found that in the absence of an image or logo, the product's attractiveness also decreases (Winstock et al., 2021).…”
Section: Cbd Product Attitudes Knowledge and Use Among Consumersmentioning
confidence: 99%